Risk of Liver Injury Associated with Intravenous Lipid Emulsions: A Prescription Sequence Symmetry Analysis - Li, Xiao-xiao; Cheng, Yin-chu; Zhai, Suo-di; Yao, Peng; Zhan, Si-yan; Shi, Lu-wen (Frontiers in Pharmacology, 2021)
Aims To determine the risk of liver injury associated with the use of different intravenous lipid emulsions (LEs) in large populations in a real world setting in China. Methods A prescription sequence symmetry analysis (PSSA) was performed using data from 2015 Chinese Basic Health Insurance for Urban Employees. Patients newly prescribed both intravenous LEs and hepatic protectors within time windows of 7, 14, 28, 42 and 60 days of each other were included. The washout period was set to one month according to the waiting-time distribution. After adjusting prescribing time trends, we quantify the deviation from symmetry of patients initiating LEs first and those initiating hepatic protectors first, by calculating adjusted sequence ratios (ASRs) and relevant 95% confidence intervals. Analyses were further stratified by age, gender, and different generations of LEs developed. Results In total, 416, 997, 1697, 2072 and 2342 patients filled their first prescriptions with both drugs within 7, 14, 28, 42 and 60 days, respectively. Significantly increased risks of liver injury were found across all time windows, and the strongest effect was observed in the first 2 weeks (ASR 6.97 [5.77-8.42] ~ 7.87 [6.04-10.61]) in overall patients. In subgroup analyses, female gender, age more than 60 years, soybean oil-based and alternative LEs showed higher ASRs in almost all time windows. Specially, a lower risk for liver injury was observed in the first 14 days following FO-LEs administration (ASR, 3.42; 95%CI, 0.81-14.47), but the risk started to rise in longer time windows. Conclusions A strong association was found between LEs use and liver injury through PSSA in a real-world setting, which aligns with trial evidence and clinical experience. Differences revealed in the risks of liver injury among various LEs needs further evaluation.